2006
DOI: 10.1128/jcm.01373-06
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Norovirus Antigens from Recombinant Virus-Like Particles and Stool Samples by a Commercial Norovirus Enzyme-Linked Immunosorbent Assay Kit

Abstract: The commercial norovirus enzyme-linked immunosorbent assay kit was evaluated for its reactivity to recombinant virus-like particles and the detection of natural viruses from stool samples of Japanese infants and children with sporadic acute gastroenteritis compared to reverse transcription-PCR. The kit had a sensitivity of 76.3% and a specificity of 94.9%. Our results clearly indicated that the kit allows the detection of the most prevalent genotype, GII/4. In order to increase the sensitivity of the kit, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The previous studies showed that the sensitivities of ELISA and IC ranged from 10 6 to 10 7 copies/g of fecal sample (4,14,25,29), while the sensitivities of the BLEIA ranged from 10 5 to 10 6 copies/g of fecal sample. Second, the BLEIA is more broadly reactive against various genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies showed that the sensitivities of ELISA and IC ranged from 10 6 to 10 7 copies/g of fecal sample (4,14,25,29), while the sensitivities of the BLEIA ranged from 10 5 to 10 6 copies/g of fecal sample. Second, the BLEIA is more broadly reactive against various genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have suggested a limited sensitivity of the NoV Ridascreen EIA kit, except for the GII.4 type (Okitsu-Negishi et al 2006, Kirby et al 2010). However, all samples tested by EIA were also tested by RT-PCR, which is a more sensitive method for detecting any NoV genotype.…”
mentioning
confidence: 99%
“…Therefore, highly sensitive assays for detecting NoV are required, and automated and rapid diagnostic systems are particularly ideal for the testing of large numbers of specimens from patients and food handlers. Many methods such as the reverse transcription polymerase chain reaction (RT‐PCR), reverse transcription loop‐mediated isothermal amplification (RT‐LAMP), real‐time RT‐PCR, enzyme‐linked immunosorbent assays (ELISA), and immunochromatoassays have been developed and used for this purpose [Kojima et al, ; Kageyama et al, ; Fukuda et al, ; Okitsu‐Negishi et al, ; Mutoh et al, ]. However, these methods are labor‐intensive.…”
Section: Introductionmentioning
confidence: 99%